STM-SEM combination study on the electrochemical growth mechanism and structure of gold overlayers: A quantitative approach to electrochemical metal surface roughening - Vazquez, Luis (1989)
The growth mode and structure of gold overlayers resulting from the electroreduction of thick oxide films are studied using potentiodynamic and potentiostatic techniques combined with ex-situ STM and SEM. Electroreduction of the thick gold oxide at low overpotentials, that is slowly grown gold overlayers, results in a close-packed array of grains exhibiting a low roughness factor. Grains in the order of 100 nm of radii are formed by aggregation of small monomers. At higher overpotentials, fast grown gold overlayers, we suggest that the monomer growth results in a columnar structure terminated on rounded domes with radii ranging between 10 and 20 nm. This overlayer exhibits a roughness factor which increases according to electrodeposit height. The columnar structure is unstable decreasing its surface free energy by coalescence of small columns to form large units leading to a drastic decrease in the surface area with ageing time. A mechanism for the growth mode is proposed where the crystallite size depends on the diffusion length of the electrodepositing particles which is controlled by the applied overpotential.